Resurfacing hip replacement - An audit of activity in the United Kingdom 2002-2003 - White, S; Beard, D; Smith, E (2004)
The level of use of resurfacing hip replacement (RHR) and specific training undertaken was previously unknown in the United Kingdom. Consultant orthopaedic surgeons were audited by postal questionnaire regarding their RHR activity, training undertaken and evidence of specialisation in hip arthroplasty. Results: 19% of surgeons had performed RHR in the previous 12 months. 33% of revision hip surgeons had performed RHR. The majority of consultants performed 6-10 cases per year. 73% performed less than 20 cases per year. For training, 30% had observed RHR surgery and 23% had attended a formal course. 7.8% of those performing RHR had neither been on a course nor observed surgery. Both British Hip Society membership and the completion of a hip fellowship were associated with the frequency of RHR. Those who had completed previous hip fellowship or were BHS members performed significantly more RHR. Conclusions: RHR is currently performed by specialists. The level of use is increasing rapidly and the standard of implantation needs to be safeguarded in order to ensure that the current successful short term results are maintained in the long term. Given the steep learning curve, the lack of long-term outcome and concerns regarding metal-on-metal bearings, we believe that the implant should continue to be used in accordance with NICE guidelines and that implantation should be performed by surgeons with a specialist interest in hip arthroplasty and specific training. © Wichtig Editore, 2004.